2016
DOI: 10.1152/ajpregu.00198.2015
|View full text |Cite
|
Sign up to set email alerts
|

Diminished anabolic signaling response to insulin induced by intramuscular lipid accumulation is associated with inflammation in aging but not obesity

Abstract: The loss of skeletal muscle mass is observed in many pathophysiological conditions, including aging and obesity. The loss of muscle mass and function with aging is defined as sarcopenia and is characterized by a mismatch between skeletal muscle protein synthesis and breakdown. Characteristic metabolic features of both aging and obesity are increases in intramyocellular lipid (IMCL) content in muscle. IMCL accumulation may play a mechanistic role in the development of anabolic resistance and the progression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(102 citation statements)
references
References 55 publications
2
97
0
3
Order By: Relevance
“…A muscle defect in the activation of the insulin meta bolic pathway (Akt phosphorylation) was identified as an early mechanism of insulin resistance development in these populations (Amouzou et al 2016). Along with the study by Amouzou et al, recent animal data has also suggested the existence of alternative mechanisms, independent of previously proposed skeletal muscle inflammation, to generate insulin resistance (Evers-van Gogh et al 2016; Rivas et al 2016). If we consider that skeletal muscle macrophages have a critical role in promoting muscle recovery and regeneration (Chazaud 2016), we might speculate that there could be an impaired ability to mediate muscle regeneration among obese individuals.…”
Section: Discussionmentioning
confidence: 80%
“…A muscle defect in the activation of the insulin meta bolic pathway (Akt phosphorylation) was identified as an early mechanism of insulin resistance development in these populations (Amouzou et al 2016). Along with the study by Amouzou et al, recent animal data has also suggested the existence of alternative mechanisms, independent of previously proposed skeletal muscle inflammation, to generate insulin resistance (Evers-van Gogh et al 2016; Rivas et al 2016). If we consider that skeletal muscle macrophages have a critical role in promoting muscle recovery and regeneration (Chazaud 2016), we might speculate that there could be an impaired ability to mediate muscle regeneration among obese individuals.…”
Section: Discussionmentioning
confidence: 80%
“…Accumulation of intramuscular lipids plays a pathogenic role in insulin resistance and type 2 diabetes . Finally, several recent studies highlighted the involvement of fatty acids and their metabolites, such as DAG and ceramides, in blocking muscle growth and altering myofiber metabolism . For this reason, we investigated how the modulation of Plin2 expression could affect the lipid metabolites in adult skeletal muscle and whether this can account for the observed effect on myofiber size.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, increased IMCL storage results in the accumulation and dysregulation of detrimental lipid intermediates such as diacylglycerols (DAGs) and ceramides, and those intermediates lead to insulin resistance through activation of protein kinase C (PKC) . High levels of DAG and ceramides have also been suggested to play a role in the development of muscle loss . In C2C12 and L6 myotubes, treatment with the fatty acid palmitate induced ceramide accumulation, and this was associated with increased expression of pro‐atrophic genes such as atrogin‐1/MAFbx, increased levels of FoxO3, upregulated eIF2α phosphorylation, and decreased protein synthesis .…”
Section: Determinants Of Muscle Massmentioning
confidence: 99%